Social perceptions and the stigmatization towards fifteen mental illnesses in France: a preliminary study on the role of vital force and burden - Dambrun, Michael; Marinho, Gaétan; Mondillon, Laurie; Clinchamps, Maélys; Dutheil, Frédéric; Chakroun, Nadia; Teissedre, Frédérique; Motak, Ladislav; Corman, Maya; Cuchet, Isabelle; Fargheot, Juliette; Izaute, Marie; et al. (Frontiers in Psychiatry, 2024)
Introduction. This study examined social perceptions and rejection towards fifteen mental ill-nesses, as well as a preliminary test of the SUBAR model, that hypothesized perceptions of both vital forces and burden would be negatively and positively related to social rejection, re-spectively. Methods. Using an online survey with participants from France (n = 952), social rejection was assessed using a feeling thermometer and a social distance scale, while social perceptions were measured using visual analog scales. Results. A stigma map for these different disorders is drawn up, revealing the social percep-tions and levels of stigmatization specific to certain mental illnesses. Controlling for relevant social perceptions (i.e., danger, warmth, competence), we found that perception of burden was positively and significantly associated to social distance and negative feeling for 73% and 67% of mental illnesses, respectively. The perception of vital force was negatively and significantly related to social distance and negative feeling for 87% and 20% of mental illnesses, respectively. The change in R2 between model 1 (i.e. perception of danger, warmth, competence) and model 2 (i.e. model 1 + perceptions of vital force and burden) significantly improved in 100% of cases for social distance and 67% of cases for negative feeling. Conclusion. These preliminary data provide support for the SUBAR model and call for further investigations to better understand the social rejection of people with mental illnesses.